2018
DOI: 10.1158/1078-0432.ccr-17-1172
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Pharmacogenomic Profiling of Malignant Pleural Mesothelioma Identifies a Subgroup Sensitive to FGFR Inhibition

Abstract: Despite intense research, treatment options for patients with mesothelioma are limited and offer only modest survival advantage. We screened a large panel of compounds in multiple mesothelioma models and correlated sensitivity with a range of molecular features to detect biomarkers of drug response. We utilized a high-throughput chemical inhibitor screen in a panel of 889 cancer cell lines, including both immortalized and primary early-passage mesothelioma lines, alongside comprehensive molecular characterizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…They also showed an association between BAP1 loss and increased expression of the receptors FGFR1/3 and ligands FGF9/18. 29 Taken together with these reports, our study indicates the possibility that the FGF-FGFR axis could play an important role in the molecular pathogenesis of MPM.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…They also showed an association between BAP1 loss and increased expression of the receptors FGFR1/3 and ligands FGF9/18. 29 Taken together with these reports, our study indicates the possibility that the FGF-FGFR axis could play an important role in the molecular pathogenesis of MPM.…”
Section: Discussionsupporting
confidence: 83%
“…Recent data reported by The Cancer Genome Atlas lung squamous cell carcinoma project showed that the FGFR tyrosine kinases are some of the most frequently altered kinase families in lung squamous cell carcinoma . Interestingly, Quispel‐Janssen et al recently reported that a subgroup of immortalized and primary MPM lines appeared to be highly sensitive to FGFR inhibition. They also showed an association between BAP1 loss and increased expression of the receptors FGFR1/3 and ligands FGF9/18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C,D). Significant cell death in the absence of caspase‐3/7 activity has been reported in several other FGFR‐dependent models including breast cancer (CAL51) (Sharpe et al ., ) and mesothelioma (H2810) (Quispel‐Janssen et al ., ). Although caspase and/or PARP cleavage following FGFR inhibition has been reported in several gastric and breast models (Kunii et al ., ; Pearson et al ., ), it has only been reported in one liver cell line (Hep3B) (Hagel et al ., ) and one lung cancer cell line (H1581) (Goke et al ., 2015a) with caspase‐independent death also being reported in the latter.…”
Section: Discussionmentioning
confidence: 99%